Semantic data mining an ontology-based approach - Lawrynowicz, Agnieszka (Studies on the semantic web ;, 2017)
The book is devoted to semantic data mining--a data mining approach where domain ontologies are used as background knowledge, and where the new challenge is to mine knowledge encoded in domain ontologies and knowledge graphs, rather than only purely empirical data.